The Effect of Body Mass Index on Outcome Following Ambulatory High Ligation and Stripping for Lower Varicose Veins: A Prospective Cohort Study - Chen, Chu Wen; Cai, Yu T.; Wang, Jia R.; Wu, Zhou P.; Liu, Yang; Huang, Bing; Yang, Yi; Yuan, Ding; Ma, Yu K.; Zhao, Ji C. (Frontiers in Surgery, 2022)
Objectives The effects of body mass index (BMI) on the outcome of high ligation and stripping (HLS) in an ambulatory center remain unclear. This study aims to investigate the outcomes of HLS in an ambulatory center based on BMI in the Chinese population. Design This was a prospective cohort study with mid-term follow-up. Materials and Methods 170 eligible patients were included in the study and the data of Clinical, Etiology, Anatomy, and Pathophysiology (CEAP) classification, Venous Clinical Severity Score (VCSS), Visual Analogue Score (VAS), Aberdeen Varicose Veins Questionnaire (AVVQ), Quality of Recovery (QoR-15), and postoperative complications at predetermined time points were collected. Results A total of 170 patients (236 limbs) with a mean age of 53.87 ± 9.96 years (range, 24–80 years) and a mean BMI of 23.86 ± 2.96 kg/m2 were included. Of the group, 50.6% were women, and 66 patients received bilateral procedures. Through curve fitting, a BMI less than 28 and a BMI of 28 or higher were found to have a negative [−0.1 (−0.3, 0.1) 0.296] and positive [0.7 (0.2, 1.2) 0.006] relationship trend, respectively, with the improvement of VCSS at 6 weeks after surgery. Through smooth curve fitting, BMI was shown to have a negative relationship trend on the improvement of VCSS at 6 months after surgery. After multivariable risk adjustment for potential confounding factors, BMI was not found to be associated with the improvement of VCSS and AVVQ at 6 weeks after surgery, as well as the improvement of AVVQ at 6 months after surgery (all p-values >0.05). Six months after surgery, BMI was shown to have a negative relationship trend on the improvement of VCSS, and obese patients showed lower VCSS improvement than patients of normal BMI [−1.3 (−1.9, −0.7) <0.0001]. Six weeks after surgery, postoperative complications such as paresthesia were found to be significantly higher in the obese group than in the non-obese group (p < 0.05). At 6 months after surgery, the obese group showed significantly higher complications of the legs compared with the normal BMI group (p < 0.05). Conclusions Our results showed that obesity is a risk factor for prognosis and postoperative complications following ambulatory HLS.